ALLEGORICAL MEANS OF ORAL SPEECH - Rajapova Malika Ahmadali qizi (Galaxy International Interdisciplinary Research Journal, 2022)
The purpose of the article is to discuss about a stylistic device which is called “allegory” and its origin. Moreover, aricle illustrates some examples of allegories in oral speech as well as other speech styles like formal and informal.